Relational Practices in Arts-Based Research - Celeste Pang; Brittany A.E. Jakubiec; Melanie Schambach (Atlantis)
Fostering Dialogues was an arts-based action research project that brought together LGBTQ+ older adults and homecare personal support workers in a virtual arts and dialogue program to explore presents and futures of community-based care. In this Research Note the artist and researcher team reflect on the researcher-artist relationship and arts-based collaboration, touching on topics including community engagement, horizontal decision-making, and the power of images to affect change.